MANEJO POPULACIONAL DE Meloidogyne incognita EM CAFÉ CONILON - Lima, Alex Silva (2022)
Coffee growing is an agricultural activity that has great socioeconomic importance, and it is essential to maintain its productive capacity against the occurrence of diseases that interfere with its development, among which those caused by nematodes stand out. The objective of this work was to evaluate different treatments in the population management of nematodes (Meloidogyne incognita) in conilon coffee (Coffea canephora Pierre ex Froehner) and possible effects on plant vegetative development and productivity. The experiment was carried out in a coffee plantation naturally infected by the pathogen, in a randomized block design, with five treatments and six replications. Four evaluations of the population of nematodes in the soil and roots of coffee were carried out, for later evaluation of the reproduction factor. The vegetative development of plants was evaluated by periodically measuring the growth of previously marked orthotropic and plagiotropic branches and plant productivity was performed by harvesting the grains in July 2021. The treatments used provided a reduction in the reproduction factor of Meloidogyne incognita in the roots of conilon coffee plants in all periods evaluated, after the first and also after the second application of the products, while Cadusafos 200.0 g/L was responsible for the greater multiplication of the population of M. incognita in the soil after two applications. The treatment based on organomineral phosphate fertilizer provided better vegetative growth of conilon coffee, with higher growth values of orthotropic and plagiotropic branches, however, none of the treatments influenced the productivity of conilon coffee.